Strengthening Critical Thinking Skills in Civics Education through the Application of the Socrates Seminar Learning Model - Zulkifli Alamsah Sutanto; Mukhamad Murdiono (Universitas Pendidikan Ganesha, 2025)
Education in Indonesia evolve along with the development of society, technology, and knowledge. However, learning practices are still largely dominated by conventional lecture-based models. This study analyze the strengthening of students’ critical thinking skills through the implementation of the Socratic seminar learning model. The research employed a case study with a qualitative approach. The subjects were Pancasila and Citizenship Education (PPKn) teachers and eleventh-grade students. Data were collected through interviews, observations, and documentation using instruments such as interview guidelines, observation sheets, and document checklists. Data analysis included condensation, display, and verification. The results show that the implementation of the Socratic seminar effectively strengthened students’ critical thinking skills through several aspects: (a) developing indicators and problems suited to students’ abilities, (b) encouraging students to answer teachers’ questions by expanding their responses based on the material studied, (c) utilizing printed and electronic media as learning resources, and (d) enabling students to explore material independently according to their own understanding. The conclusion emphasizes that the Socratic seminar model not only trains students to enhance critical thinking skills but also encourages teachers to act as innovators, role models, and evaluators in strengthening students’ critical thinking in PPKn learning. This research provides guidance for teachers, particularly PPKn teachers, in selecting learning models that align with student characteristics, thereby creating more effective, contextual, and critical thinking-oriented learning.